KNOWLEDGE MANAGEMENT SEBAGAI UPAYA PENGEMBANGAN LEARNING ORGANIZATION DI LEMBAGA PENDIDIKAN ISLAM - Mardia; Muhammad Mukhtar S (Department of Islamic Education Management, 2022)
Knowledge consists of two types: tacit knowledge and explicit knowledge. Tacit knowledge is a silent knowledge in the human mind in the form of intuition, judgment, skill, values, and beliefs that are difficult to share and share with others. While explicit knowledge is knowledge that can or has been codified in the form of documents or other tangible forms that can be easily transferred and distributed using various media. Explicit knowledge can be formulas, cassette /video CDs, audio, product specifications or manuals. A learning organization is an organization that: (1) has an atmosphere in which its members are individually motivated to learn and develop their potential; (2) extend this learning culture to significant customers, suppliers, and other steakholder; (3) To make human resource development strategy as the center of organizational policy; (4) to be in the process of continuous organizational transformation.